The Correlation between Service Quality and Patient Satisfaction in the Maternal Emergency Department in “Anyar Community Health Center” 2023 A Cross Sectional Study (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Overall, it is estimated that 15% of pregnant women experience serious obstetric complications and require treatment in the maternal emergency department (IGD Maternal) at the community health center (Puskesmas). However, sometimes in health services, especially in government basic service centers in Indonesia, there is interaction or delivery of information between health workers and patients or families that is not good enough to reduce patient satisfaction. The purpose of this study was to analyze the relationship between the level of patient satisfaction and the quality of maternal emergency department services. A cross-sectional study design was carried out in April 2023 at the maternal emergency department at the Community health center, Serang-Banten. The research sample consisted of 33 pregnant women who attended and had taken care of the maternal emergency department. Satisfaction and service quality were measured using a questionnaire that had been tested for validity and reliability. Chi-square bivariate analysis was performed using SPSS. Most of the patients were quite satisfied with the service (51.5%). However, assessing the quality of service is still lacking (54.5%). Statistical analysis concluded that there is a significant relationship between service quality and patient satisfaction (OR: 10.4; 95% CI (2.03 – 53.2); p value: 0.003). Good service quality will increase patient satisfaction 10 times compared to poor service quality.